Chemical Profiling of Street Dust in Kathmandu Valley: A Preliminary Environmental Assessment - Karki, Bishow; Kandel, Mani Ram; Ghimire, Muskan; Kandel, Lekh Nath; Khanal, Santosh; Bhattarai, Deval Prasad (Journal of Nepal Chemical Society, 2025)
Street dust in urban agglomerations serves as a sink and secondary source of environmental contaminants, primarily in rapidly growing urban agglomerations. This first-time study investigates the chemical properties and concentration of heavy metal in street dust samples collected from six representative sites in Kathmandu Valley, Nepal. The dust samples were analyzed for pH, electrical conductivity (EC), bicarbonate presence, organic functional groups, and concentrations of heavy metals (Zn, Pb, Cd) using standardized techniques like Fourier Transform Infrared Spectroscopy (FTIR) and Atomic Absorption Spectroscopy (AAS). Results ranged consistently alkaline pH (7.2–8.05), varying EC concentrations (0.397 × 10⁻⁶ to 0.75 × 10⁻³ S/cm), and bicarbonate ion presence at specific sites. FTIR analysis showed the presence of major organic pollutants like alkanes, aromatic hydrocarbons, and halogenated compounds that reflect diverse anthropogenic sources. AAS analysis showed zinc as the dominant heavy metal (avg. >250 mg/kg), followed by lead ( 180 mg/kg) and cadmium ( 20 mg/kg), with highly significant spatial variation attributed to land-use category. Comparison to global urban dust standards ranks Kathmandu as one of the more polluted capital cities, pointing to immense deficiencies in environmental regulation and urban planning. The findings provide required baseline data to guide pollution monitoring and suggest pressing needs for targeted mitigation action to protect public and environmental health.